Fifteen years of Servitude et Grandeur to the application of a biophysical technique in medicine: The tale of AFMBioMed. Issue 3 (18th December 2018) - Pellequer, Jean‐Luc; Parot, Pierre; Navajas, Daniel; Kumar, Sanjay; Svetličić, Vesna; Scheuring, Simon; Hu, Jun; Li, Bin; Engler, Adam; Sousa, Susana; Lekka, Małgorzata; Szymoński, Marek; et al.
Abstract: AFMBioMed is the founding name under which international conferences and summer schools are organized around the application of atomic force microscopy in life sciences and nanomedicine. From its inception at the Atomic Energy Commission in Marcoule near 2004 to its creation in 2007 and to its 10th anniversary conference in Krakow, a brief narrative history of its birth and rise will demonstrate how and what such an organization brings to laboratories and the AFM community. With the current planning of the next AFMBioMed conference in Münster in 2019, it will be 15 years of commitment to these events. Abstract : AFMBioMed is the founding name under which international conferences and summer schools are organized around the application of atomic force microscopy in life sciences and nanomedicine. From its inception at the Atomic Energy Commission in Marcoule near 2004 to its creation in 2007 and to its 10th anniversary conference in Krakow, a brief narrative history of its birth and rise will demonstrate how and what such an organization brings to laboratories and the AFM community.